Reduced glutathione biosynthesis in Drosophila melanogaster causes neuronal defects linked to copper deficiency. Issue 3 (2nd March 2016) - Mercer, Stephen W.; La Fontaine, Sharon; Warr, Coral G.; Burke, Richard
Abstract: Glutathione (GSH) is a tripeptide often considered to be the master antioxidant in cells. GSH plays an integral role in cellular redox regulation and is also known to have a role in mammalian copper homeostasis. In vitro evidence suggests that GSH is involved in copper uptake, sequestration and efflux. This study was undertaken to further investigate the roles that GSH plays in neuronal copper homeostasis in vivo, using the model organism Drosophila melanogaster . RNA interference‐mediated knockdown of the Glutamate‐cysteine ligase catalytic subunit gene ( Gclc ) that encodes the rate‐limiting enzyme in GSH biosynthesis was utilised to genetically deplete GSH levels. When Gclc was knocked down in all neurons, this caused lethality, which was partially rescued by copper supplementation and was exacerbated by additional knockdown of the copper uptake transporter Ctr1A, or over‐expression of the copper efflux transporter ATP7 . Furthermore, when Gclc was knocked down in a subset of neuropeptide‐producing cells, this resulted in adult progeny with unexpanded wings, a phenotype previously associated with copper dyshomeostasis. In these cells, Gclc suppression caused a decrease in axon branching, a phenotype further enhanced by ATP7 over‐expression. Therefore, we conclude that GSH may play an important role in regulating neuronal copper levels and that reduction in GSH may lead to functional copper deficiency in neurons in vivo . We provide genetic evidence that glutathione (GSH) levels influence Cu content or distribution in vivo, in Drosophila neurons. GSH could be required for binding Cu imported by Ctr1A and distributing it to chaperones, such as Mtn, CCS and Atox1. Alternatively, GSH could modify the copper‐binding and transport activities of Atox1 and the ATP7 efflux protein via glutathionylation of copper‐binding cysteines. Abstract : We provide genetic evidence that glutathione (GSH) levels influence Cu content or distribution in vivo, in Drosophila neurons. GSH could be required for binding Cu imported by Ctr1A and distributing it to chaperones, such as Mtn, CCS and Atox1. Alternatively, GSH could modify the copper‐binding and transport activities of Atox1 and the ATP7 efflux protein via glutathionylation of copper‐binding cysteines.